Bird observations in the Muratus Mountains, Kalimantan Selatan - G W. H Davison (Indonesian Ornithologists’ Union, 1997)
A brief survey was made of birds in the Muratus Mountains, Kalimantan Selatan, in October 1996. At least 21 montane specialists occur there. These are all first records for the area, and major extensions of known range are made for Mountain Tailorbird Orthotomus cuculatus, White browed Rhinomyias Rhinomyias gularis and Black capped White eye Zosterops atricapilla.